Metal-on-Metal Hip Retrieval Analysis: A Case Report - Thomas B. Pace; Kara A. Rusaw; Lawrence J. Minette; Brayton R. Shirley; Rebecca G. Snider; John D. DesJardins (Case Reports in Orthopedics)
This is a case report involving a single case with severe bone and soft tissue destruction in a young male patient with a 10-year-metal on-metal total hip arthroplasty. Following complete aseptic erosion of the affected hip greater trochanter and abductor muscles, the hip was revised for recurrent instability. Histological examination of the patient’s periprosthetic tissues, serological studies, and review of recent medical reports of similar cases were used to support an explanation of the destructive process and better contribute to our understanding of human reaction to metal debris in some patients following metal-on-metal hip arthroplasty.